Pelatihan dan Pendampingan Pembuatan Aplikasi Fun Exam Berbasis Komputer dan Karakteristik Mata Pelajaran Untuk Guru Madrasah Negeri Aliyah 2 Mojokerto - Ludi Wishnu Wardana; Elfia Nora; Imam Bukhori; Yuli Soesetio (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Online exam applications can be used by teachers as a medium to evaluate the level of achievement of students' understanding of these subjects. Training on making exam applications and providing knowledge about exam applications was carried out for Mojokerto 2 Madrasah Aliyah Negeri 2 teachers as one of the community service activities. Based on these training activities it is known that many teachers know about online exam applications, and have implemented them in evaluating learning assessments, but in operation there are still many who ask for help from administrative staff or other teacher colleagues who can, and manufacture test application products for Madrasah Negeri Aliyah 2 Mojokerto, After providing training to teachers and input from teachers for adding features to the application Training,Application, Fun Test, Characteristics